INVESTIGATING THE INTERPLAY OF LANGUAGE, TEXT, AND SOCIALPRACTICE: FROM TEXT LINGUISTICS TO CRITICAL DISCOURSE ANALYSIS - Kostova, Boryana (E-Journal VFU, 2024)
This article explores the convergence between Text Linguistics and Critical Discourse Analysis (CDA) by investigating how language, text, and social practice intersect. It traces the historical and theoretical underpinnings of both fields, examining their shared focus on textuality and discourse while emphasizing their distinct methodologies and objectives. Text Linguistics iscentered on the formal properties of texts, such as cohesion and coherence, while CDA seeks to uncover the sociopolitical implications of discourse. The analysis highlights the complementary nature of these approaches and their relevance in studying communication within diverse contexts, including media, advertising, legal and political discourse.
Keywords: social practice; textuality; Critical Discourse Analysis; Text linguistics